The musical scene in Uganda views from without and within - Cooke, Peter; Kasule, Sam (International Library of African Music, 1999)
This article is a collaborative effort between a Ugandan scholar specialising in theatre studies and currently teaching in the United Kingdom and a British ethnomusicologist who taught in Uganda during the 1960s and has since maintained his musical research interests there. Firstly we present a composite view of musical life in Uganda. Later in the paper we present our own separate ideas (even where they overlap).
Keywords: African Music; Uganda